2003
DOI: 10.4049/jimmunol.171.10.5406
|View full text |Cite
|
Sign up to set email alerts
|

Peritoneal Cavity B Cells Are Precursors of Splenic IgM Natural Antibody-Producing Cells

Abstract: Peritoneal cavity B-1 cells are believed to produce IgM natural Abs. We have used α1,3-galactosyltransferase-deficient (GalT−/−) mice, which, like humans, produce IgM natural Abs against the carbohydrate epitope Galα1,3Gal (Gal), to demonstrate that peritoneal cavity B-1b cells with anti-Gal receptors produce anti-Gal IgM Abs only after LPS stimulation. Likewise, peritoneal cavity cells of GalT−/− and wild-type mice do not produce IgM Abs of other specificities without LPS stimulation. Development of Ab-secret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
108
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(120 citation statements)
references
References 47 publications
12
108
0
Order By: Relevance
“…5A). The facts that PC1 lo cells migrate more readily to the spleen than PC1 hi cells and that peritoneal B-1 cells become secretory only after migration to the spleen (20) suggested that PC1…”
Section: Pc1mentioning
confidence: 99%
See 1 more Smart Citation
“…5A). The facts that PC1 lo cells migrate more readily to the spleen than PC1 hi cells and that peritoneal B-1 cells become secretory only after migration to the spleen (20) suggested that PC1…”
Section: Pc1mentioning
confidence: 99%
“…These antibodies are encoded by "stereotyped" germ-line sequences and can be of IgM, IgG, or IgA classes. The lymphoid compartments in which B-1a cells secrete natural antibodies have been shown to include the spleen and BM (20)(21)(22). Recently, Cole et al showed that spleens of mice immunized with the atypical LPS of Francisella tularensis contain antigen-specific plasma cells of B-1a origin (23).…”
Section: B-1 Cells | Natural Antibody | Innate Immunity | B Regulatormentioning
confidence: 99%
“…6 Left). Discussion B-1a cells are very important players in both innate and adaptive immunity (1,(14)(15)(16)(17)(18)(19). In mice that have not been intentionally immunized or infected, they produce much of the ''natural'' serum IgM and, in mice stimulated with LPS or other microbial products, they produce much of the polyclonal antibody response (2,3,20).…”
Section: B-1a Cells That Migrate From Perc To the Spleen Divide Beformentioning
confidence: 99%
“…Like B1b cells, these cells bridge the innate and adaptive immune systems, because they have the capacity to respond to specific foreign Ag more rapidly than conventional T and B lymphocytes (10). MZB cells can be distinguished from follicular B cells by their complement receptor 2 (CD21) high CD1d high CD23 low phenotype (11,12) and from splenic B1 B cells by their CD21 high CD43 low expression (13). Based on studies using inert particles and heat-killed bacteria, it has been postulated that reduced CD23 expression, a negative regulator of B cells, may allow MZB cells to produce a more rapid Ab response compared with follicular B cells, and that CD21 high expression facilitates MZB cell interaction with complementcoated blood-borne Ag (14).…”
mentioning
confidence: 99%